Thalassemia in Iraq Review Article - Khaleed J . Khaleel (Iraqi Journal of Cancer and Medical Genetics, 2020)
Thalassemia major is quite prevalent in Iraq with about 15000 patients. Thalassemia is big health issue that have very big burden on health services. In Iraq 19 thalassemia center that reflects the importance of disease. Premarital testing for thalassemia is of prime importance of awareness of couples about the risk of getting the disease to their offspring and the complications of the disease. Education program is also important using mass media leaflets and posters about the importance of prevention of the disease